Promoting critical thinking through simulation-based healthcare training (SBHT): A scoping review - K Henrico; N Oostdam (African Journal of Health Professions Education, 2022)
Background. Critical thinking (CT) is an essential graduate attribute for health professions (HP) students. Yet, achieving a higher level of CT in HP students through education is often difficult for educators. SBHT has proven to be an effective strategy to promote CT, but it is not clear how this educational pedagogy should be implemented to achieve higher levels of CT. Objective. To identify and describe the use of simulation-based healthcare training (SBHT) strategies to promote CT in HP students.